Random nanocrack, assisted metal nanowire-bundled network fabrication for a highly flexible and transparent conductor. Issue 62 (14th June 2016) - Suh, Young D.; Hong, Sukjoon; Lee, Jinhwan; Lee, Habeom; Jung, Seongmin; Kwon, Jinhyeong; Moon, Hyunjin; Won, Phillip; Shin, Jaeho; Yeo, Junyeob; Ko, Seung Hwan
Abstract : Bundled metal nanowire network transparent conductor with enhanced mechanical characteristics was fabricated from random crack patterns. Abstract : The most viable flexible and transparent conductor alternative to indium tin oxide (ITO) is metal mesh on plastic including metal micro-lines at regular spacing and metal nanowire percolation networks. Applications in flexible and transparent devices have been hampered by either moiré pattern problems caused by regular patterning or low mechanical robustness of the nanowire network. In this study, we demonstrate a novel class of flexible transparent conductor based on metal nanowire micro-bundled networks at random patterns. Original random patterns are prepared from controlled random cracking of high-stress silicon nitride on the silicon substrate, and employed as repetitively usable master molds with independently controllable pattern density and linewidth. Silver nanowires are subsequently placed in the random crack channels through a facile solution process and transferred to the polymer substrate with UV curable epoxy resin. The resultant flexible and transparent conductor, spanning over wafer scale at high reproducibility, not only exhibits enhanced mechanical robustness upon repeated bending or scratching, which often occurs when used as touch-screen panel, but also is free from the moiré pattern problem due to the random nature of nanowire bundle patterns. Further application of the resultant flexible transparent conductor as a touch-screen panel confirms easy large-scale fabrication of this robust and flexible transparent conductor.